"An Indelible Mark": Gay Purges in Higher Education in the 1940s. Issue 4 (November 2015) - Nash, Margaret A.; Silverman, Jennifer A. R.
Abstract : In June 1948, Wisconsin Superior Court Judge Roy H. Proctor sentenced four University of Wisconsin students to one year probation for "participating in abnormal sexual activities." The four students were among a group of twelve men on and off campus who had been arrested by city and university police. Their sentence was mild, given that the judge could have put them in prison for up to five years. Judge Proctor warned them that if there was a second offense, they should not expect leniency. "Each and all of you should feel deeply ashamed, " Proctor told them; "your conduct has caused an indelible mark to be placed against you. Certainly you will have to watch your step in the future, not only to avoid becoming second offenders, but to allay all suspicions of your becoming involved again." Indeed, when one of the young men tried to move on with his life, university administrators made sure that the "indelible mark" followed him.